Avaliação dos efeitos biológicos e tóxicos de plantas do Cerrado : um enfoque em Vernonanthura polyanthes - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
The Cerrado has a wide variety of medicinal plants that are used for the treatment of various diseases. The first objective of this work was to perform a systematic review on the toxic potential of these species. Our search in the literature identified 194 Cerrado plants with toxic potential, and most of the species presented compounds with high cytotoxicity against tumor cells and low toxicity against normal cells. Regarding the interaction with DNA, compounds extracted from Cerrado plants in acute and/or chronic treatments showed low genotoxicity andmutagenicity. Antibactericidal, antifungal, antiviral, insecticidal and antiparasitic activities were also identified in different extracts from Cerrado plants. Among the different species identified in our review, this thesis is of special interest in Vernonanthura polyanthes(Spreng.)A.J. Vega & Dematt, popularly known as assa-peixe. This species is widely used in folk medicine as an expectorant. Our research group previously showed that V. polyanthes aqueousextract (VpLAE) and n-butanol fraction (n-BF) were cytogenotoxic against human lymphocytes. However, when co-treatedwith doxorubicin (DXR), VpLAE and n-BF decreasedDXR genotoxicity. Thus, another objective of this thesis was to evaluate the chemical profile by mass spectrometry and toxicology of VpLAE and n-BF and their interaction with DXR in amurine model using micronucleus (MN) and comet assay techniques. Our analysis identified the presence of 8 phenolic compounds characterized as flavonoids and chlorogenic acids (5-O-feruloylquinic acid, quercetin 3-O-rutinoside, 3,4-di-O-caffeoylquinic acid, 3,5-di-O- cafeoylquinic acid , 4,5-di-O- caffeoylquinic acid, 3-O-caffeoylquinic acid, 5-O-caffeoylquinicacid and 4-O-caffeoylquinic acid). At co, pre and post DXR treatment, both VpLAE and n-BF significantly inhibited DXR toxicity, protecting mouse bone marrow cells against cytotoxic, genotoxic and mutagenic effects. Another objective of this research was to perform computational prediction to predict their biological activities of the 8 compounds identified VpLAE and n-BF by mass spectrometry. The in silico results are in agreement with our in vivo in murines, showing that the identified compounds proved to be chemopreventive and antioxidant. In particular, the molecule quercetin-3-O-rutinoside (Rutin) identified in VpLAE and n-BF showed anticancer potential, in addition to presenting low penetration through the blood-brain barrier (BBB) and median lethal dose (LD50) with a value of 5000 mg/ kg, representing a safe margin, since the compound was classified in class 5. These properties led to the choice of rutin for molecular docking analysis and demonstrated a promising antineoplastic, antimutagenic and/or cancer preventive interaction, according to the PASS online prediction. In conclusion, these results reinforce the chemopreventive and antioxidant potential of V. polyanthes species.
Assessment of the biological and toxic effects of Cerrado : a focus on Vernonanthura polyanthes
Keywords: Estresse oxidativo; Assa-peixe; Ensaio cometa; Micronúcleo; Rutina; Produtos naturais; Docking molecular; Pass online; Vernonanthura polyanthes; Oxidative stress; Assa-peixe; Comet assay; Micronucleus; Routine; Products natural; Molecular docking; PASS online; CIENCIAS BIOLOGICAS; OUTROS